Turkish adaptation of the comprehensive inventory of mindfulness experiences-adolescents: A reliability and validity study - EKŞİ, HALİL (E D P SCIENCES, 2018)
In this study, it was aimed to adapt the Comprehensive Inventory of Mindfulness Experiences-Adolescents into Turkish, and to analyze the measure's validity and reliability. The sample of the study consisted of 415 high school students. Confirmatory factor analysis confirmed the original eight-factor structure. Cronbach alpha coefficient for the overall scale is 0.70 and the coefficients differ from 0.48 to 0.69 for the sub-scales. Corrected item-total correlations are found to be between 0.20 and 0.55. The convergent and divergent validity was examined and statistically significant relations were found. The study showed that the Turkish adaptation of The Comprehensive Inventory of Mindfulness Experiences-Adolescents is a reliable and valid scale for measuring mindfulness in adolescents.
Keywords: BENEFITS